2013
DOI: 10.1002/dta.1558
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of the incorporation mechanisms of zolpidem in fingernails

Abstract: Nails are attracting increasing interest in forensic toxicology as an alternative to hair. The goal of this study was to systematically investigate the incorporation of drugs in fingernails after single drug dose, exemplified for zolpidem. Fingernail samples from ring fingers were collected one week before, and then 24 h and weekly after intake for a period of three to five months. Hair samples were taken six weeks after intake. Nail specimens were pulverized and extracted with methanol (internal standard: zol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…In two previous studies, it was demonstrated that a single drug dose is detectable in fingernail clippings [20,19]. The present study describes nail findings following two MDMA administrations.…”
Section: Mdma and Mda In Nail Samples And Comparison To Hairmentioning
confidence: 56%
See 4 more Smart Citations
“…In two previous studies, it was demonstrated that a single drug dose is detectable in fingernail clippings [20,19]. The present study describes nail findings following two MDMA administrations.…”
Section: Mdma and Mda In Nail Samples And Comparison To Hairmentioning
confidence: 56%
“…There was no relationship between drug concentrations in nail samples and days passed after the first or second MDMA intake. Nail incorporation takes place via nail matrix and nail bed [20,19]. In nail clipping drugs can be detected earlier after incorporation via nail bed than via nail matrix.…”
Section: Mdma and Mda In Nail Samples And Comparison To Hairmentioning
confidence: 99%
See 3 more Smart Citations